CO2 emissions and militarisation in G20 countries: panel cointegratrion and causality approaches - Bildirici, Melike (INDERSCIENCE ENTERPRISES LTD, 2019)
This paper aims to test the relation among militarisation, CO2 emission, economic growth, and energy consumption in G20 countries from 1965 to 2016 via panel methods. Long and short-run coefficients and the causal relationship between the variables showed the importance of energy policy and strategy for G20 countries. Due to the importance of energy policy and strategy for G20 countries, the results were not obtained by one testing approach; instead, several tests were compared. The cointegration among CO2 emissions, militarisation, energy consumption, and economic growth was determined by using Pedroni, Kao, and PARDL methods. Further, pairwise stacked common coefficient panel causality test and Dumitrescu-Hurlin causality test were applied and unidirectional causalities from militarisation to CO2 emissions and from energy consumption to CO2 emissions were determined. Furthermore, it was determined there is the evidence of bi-directional causal relationship between per capita GDP and militarisation, between per capita GDP and energy consumption, and unidirectional causality from militarisation to energy consumption. This paper recommends that environmental and energy policies must recognise the differences in the relation among militarisation, energy consumption, and economic growth in order to maintain sustainable economic growth in the G20 countries.
Keywords: environmental pollution; economic growth; energy consumption; militarisation; Pedroni test; Kao; PARDL; Dumitrescu and Hurlin causality test; CARBON-DIOXIDE EMISSIONS; ECONOMIC-GROWTH; ENERGY-CONSUMPTION; KUZNETS CURVE; ENVIRONMENTAL-QUALITY; ECOLOGICAL FOOTPRINTS; OIL CONSUMPTION; DESTRUCTION; TREADMILL; CHINA; Energy & Fuels; Engineering